THE EFFECTIVENESS OF HEALTH PROTOCOL AND COVID-19 PREVENTION ADVERTISEMENTS USING CUSTOMER RESPONSE INDEX (CRI) ON THE COMMUNITY IN BANJARMASIN CITY - Rahmatul Jannatin Naimah; Rudy Haryanto; Muhammad Wahyu Wardhana (Politeknik Negeri Bengkalis, 2021)
The aim of this research is to determine the Awareness, Comprehend, Interest, Intention, and Action levels of people in Banjarmasin City regarding the Covid-19 prevention and health protocol through advertisements. It also aims to measure the effectiveness of this advertisement using the Customer Response Index (CRI). This research used the quantitative descriptive approach and was carried out in Banjarmasin City in August 2020 using a total sample size of 100 people. The sample comprised males and females above the age of 18 and ever saw the advertisement of health protocol and covid-19 prevention on national and local TV stations or social media. Data were obtained from the respondents using online questionnaires developed based on CRI dimensions. The result showed that the people in Banjarmasin have 79% of Awareness, 91% of Comprehend, 92% of Interest, 76% of Intention, and 93% Action after seeing the Covid-19 advertisement. Furthermore, the Customer Respond Index (CRI) was 46.75% and quite effective, while the Awareness and Intention received the lowest response among all CRI dimensions. Thus, in the future, these two variables should be further improved.